PENGARUH AIR REBUSAN DAUN MAMPELAS (Tetracera indica Merr.) TERHADAP KADAR KOLESTEROL DARAH MENCIT - Dian Samitra; Zico Fakhrur Rozi (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Tetracera indica Merr. locally known as Mampelas is commonly used in traditional remedies. It believed to have the potential to cure hypercholesterolemia. The potential use of this plant to lower blood cholesterol level was understudied; therefore this study aimed to determine the effect of the infusion of fresh leaves of Tetracera indica to the blood cholesterol levels of mice. This research was true experimental design, a post-test only design with nonequivalent (control) groups. This study used 25 male mice divided into five categories, i.e., P0 mice were administered with 0 g of infusion, P1 mice with 2 g infusion, P2 mice with 5 g infusion, P3 mice with 10 g infusion, and P4 mice without Tetracera indica infusion but 10 mg of simvastatin. The treatment in all categories were given continuously for seven days. The results showed the mean of the blood cholesterol levels were 169.4 ± 59.37 mg/dL in P0, 121.8 ± 7.62 mg/dL in P1, 136.2 ± 15.69 mg/dL in P2, 110.6 ± 37 , 01 mg/dL in P3 , and 179,0 ± 35,24 mg/dL in P4. Kruskal Wallis test was calculated to determine the difference of blood cholesterol level among all groups, and it reported p < 0.05. The results of this study showed that infusion of Tetracera indica leaf was significantly lowered the level of blood cholesterol in mice.